Post-Pubertal Treatment Of Skeletal Open Bıte - Ayşegül Köklü; Zahir Altuğ; Verda Kural; Oğuz Yılmaz (Galenos Yayinevi, 1988)
During the early periods of growth, skeletal open bites are usually treated by functional appliences. Cases showing thoroughly completed growth patterns require the related treatment to differ into an extraction combinated mechanic technique even if the dental arch shows a non-crowding alignment, for extractions basically aim the reducement of anterior open bite. Since in such cases maximum anchorage is not preffered, the closure of the extraction sites are to be made either by the anterior drift of the posterior teeth or by the drift of both posterior and anterior teeth towards the extraction site. In this article; the treatment of three young female patients is presented.